2012
DOI: 10.1002/adsc.201200632
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functionalization of Unsymmetrical Arylsulfonyl Bisindoles and Bisbenzazoles

Abstract: A three‐component coupling of two different benzazole compounds with p‐toluenesulfinic acid allows the efficient preparation of unsymmetrical arylsulfonyl bisbenzazole derivatives. Substitution of the arylsulfonyl group from these adducts using sodium borohydride leads to the corresponding bisbenzazoles. Functional implementation of the bisbenzazole system can be achieved using Grignard and Reformatsky reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Bhuyan and co‐workers reported that these derivatives could be synthesized under catalyst‐free conditions, but N , N ‐dimethylbarbituric acid was inevitably formed as a byproduct [Scheme , LgH (Lg = leaving group) = N , N ‐dimethylbarbituric acid] . Other similar examples have also been reported by You and Petrini for the preparation of unsymmetrical bis(3‐indolyl)methanes. In these cases, Friedel–Crafts alkylations of α‐(3‐indolyl)benzylamines and aryl (3‐indolyl)methyl sulfones with indoles in the presence of a Brønsted acid generated tosylamide and p ‐toluenesulfinic acid, respectively, as the byproduct [Scheme , LgH = TsNH 2 (Ts = para ‐toluenesulfonyl), TsH].…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Bhuyan and co‐workers reported that these derivatives could be synthesized under catalyst‐free conditions, but N , N ‐dimethylbarbituric acid was inevitably formed as a byproduct [Scheme , LgH (Lg = leaving group) = N , N ‐dimethylbarbituric acid] . Other similar examples have also been reported by You and Petrini for the preparation of unsymmetrical bis(3‐indolyl)methanes. In these cases, Friedel–Crafts alkylations of α‐(3‐indolyl)benzylamines and aryl (3‐indolyl)methyl sulfones with indoles in the presence of a Brønsted acid generated tosylamide and p ‐toluenesulfinic acid, respectively, as the byproduct [Scheme , LgH = TsNH 2 (Ts = para ‐toluenesulfonyl), TsH].…”
Section: Introductionsupporting
confidence: 72%
“…The indole scaffold is an important and versatile structural motif that is frequently found in numerous biologically active natural products, pharmaceuticals, and functional materials. [1][2][3][4][5][6][7] Among these indole derivatives, bis(3-indolyl)alkanes, an important class of bioactive metabolites of terrestrial or marine origin, are ubiquitous in many natural products. [2] Thus, the development of a strategy for the efficient construction of bis(3-indolyl)alkanes has been actively pursued.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to verify the reactivity of indoles with different 3‐formyl benzazole compounds 34 to obtain arylsulfonyl bisbenzazoles 35 . The usual reaction conditions were applied to that reaction to provide evidence of an efficient preparation of sulfonyl bisbenzazole derivatives 35 (Scheme ) 47. To obtain satisfactory yields of these adducts, N‐protected 3‐formylbenzazoles must be used, although no limitation has been observed for the reactivity of the indole system.…”
Section: Reaction With Organometallic Compounds and Reducing Reagentsmentioning
confidence: 99%
“…The reaction of aryl bisbenzazoles 35 with Grignard reagents described in the previous section, although interesting, is unable to provide a valuable degree of functionalization in the obtained bisbenzazole derivatives. For this reason, a Reformatsky‐like process using selected α‐bromo derivatives 46 has been pursued to install useful functional groups amenable to further synthetic transformations (Scheme ) 47. α‐Bromoketones and α‐bromoesters give satisfactory results in the reaction with substrates 35 and, notably, even bromoacetonitrile is reactive under our devised reaction conditions.…”
Section: Reaction With Enolate Systemsmentioning
confidence: 99%